2022
DOI: 10.3390/foods11020201
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes You Get Good Ones, and Sometimes You Get Not-so-Good Ones”: Vendors’ and Consumers’ Strategies to Identify and Mitigate Food Safety Risks in Urban Nigeria

Abstract: This paper uses detailed data from in-depth interviews with consumers (n = 47) and vendors (n = 37) in three traditional markets in Birnin Kebbi, Nigeria. We used observations from those markets to examine how consumers and vendors identify and avoid or manage food safety risks and whom they hold responsible and trust when it comes to ensuring food safety. At the level of the vendor, consumers mentioned seeking “clean” or “neat” vendors or stalls. Cleanliness was primarily related to the appearance of the vend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…In Phase 2, they focused on vendors’ motivations for selling food, how food safety related to collaboration and competition among vendors, customer relations, and on specific cues vendors used to address quality and safety for fish and GLV. Not all topics are covered here; some are explored in a companion paper [ 32 ]. All interviews also covered sociodemographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…In Phase 2, they focused on vendors’ motivations for selling food, how food safety related to collaboration and competition among vendors, customer relations, and on specific cues vendors used to address quality and safety for fish and GLV. Not all topics are covered here; some are explored in a companion paper [ 32 ]. All interviews also covered sociodemographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Levi [51] posited that the goodwill of the government is an important component of government trust, representing the extent to which the government cares for people's livelihoods and interests, as measured by the motivations and goals of government management behavior. To a large extent, consumers believe that the government is responsible for ensuring food safety [52] and should take responsibility for disclosing food safety information and communicating risk. National food safety monitoring and inspection departments should regularly publish relevant information and undertake risk monitoring.…”
Section: Hypothesis 121 Effect Of Institutional Trust On Attitudementioning
confidence: 99%
“…Consumers' perspectives about food safety rely partly on the food's smell, taste, attributes, and appearance as criteria for safe food consumption [9,13,[15][16][17]. Prinsen et al [18] indicated that a food's appearance held higher value than how it was processed and stored.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers attributed increases in disease prevalence to food-safety concerns, such as chemicals, contaminants, and adulteration, rather than concerns related to the nutritional content of the packaged food [ 6 ]. Barriers associated with purchasing safe food products included affordability [ [6] , [7] , [8] , [9] , [10] ], availability [ 7 , 9 , 11 , 12 ], and the effectiveness of institutions regulating food safety [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation